Importance of the vessel distribution at splenic hilum for laparoscopic Warshaw procedure - Ono, Shinichiro; Adchi, Tomohiko; Kitasato, Amane; Hidaka, Masaaki; Soyama, Akihiko; Natsuda, Koji; Hara, Takanobu; Pravisani, Riccardo; Takatsuki, Mitsuhisa; Kuroki, Tamotsu; Eguchi, Susumu (International Surgery Journal, 2021)
The laparoscopic Warshaw procedure (LWP) is a considered to carry a risk of splenic infarction and perigastric varices formation. We retrospectively analyzed the clinical outcomes and relationship between the distribution of the splenic hilum vessels and splenic infarction in patients who underwent LWP from February 2007 to February 2017. A total of 19 patients underwent LWP, and the median follow-up duration was 78 months. The median operative time and blood loss were 295 min and 200 gr. Six patients with splenic partial infarction and 3 with gastric varices were detected, but they have not needed any treatments. According to the classification by Michels, the distribution of splenic vessels were divided as distributed type and magistral type at the splenic hilum. In our study, 16 patients were distributed type and 3 were magistral type. Three of the 16 patients developed splenic infarction in distributed type. In contrast, all of magistral patients showed splenic infarction. Although LWP is a safe procedure, there is a high risk of splenic infarction if the splenic vessel distribution is a magistral type. Understanding the type before surgery leads to the identification of an appropriate vascular dissection position and reduces postoperative complications.